Association of blood mercury levels with nonmelanoma skin cancer in the U.S.A. using National Health and Nutrition Examination Survey data (2003–2016). (5th February 2020) - Rhee, J.; Vance, T.M.; Lim, R.; Christiani, D.C.; Qureshi, A.A.; Cho, E.
Summary: Background: Some studies have reported increased incidence or mortality of lung and brain cancers associated with occupations involving potential mercury exposure. Epidemiological evidence related to skin cancer is also limited. Objectives: To investigate the association between blood mercury (Hg) levels and nonmelanoma skin cancer (NMSC). Methods: We used National Health and Nutrition Examination Survey data from 2003 to 2016. The exposures were blood total (tHg), inorganic (iHg) and methylmercury (MeHg). The outcome was a self‐reported diagnosis of NMSC. We included participants aged ≥ 20 years who had information on blood mercury and sociodemographic factors. We conducted a logistic regression analysis to estimate odds ratios (ORs) and 95% confidence intervals (CIs) for the risk of NMSC associated with quartiles of blood Hg, after adjusting for the sociodemographic factors and survey year. Results: The number of participants was 29 413; mean age was 49 years and 52% were female. Compared with those with a tHg ≤ 0·47 μg L −1 (Q1), those with a tHg > 1·74 μg L −1 (Q4) had nearly double the odds of NMSC (OR 1·79, 95% CI 1·19–2·71; P trend = 0·004). Similarly, those in the highest quartile of MeHg (> 1·44 μg L −1 ) had 1·7 times greater odds of NMSC (OR 1·74, 95% CI 1·13–2·70; P trend = 0·01) than those in the lowest quartile (≤ 0·21 μg L −1 ). iHg levels were nonsignificantly positively associated with NMSC ( P trend = 0·08). Conclusions: We found that higher blood tHg and MeHg levels were associated with a higher prevalence of NMSC. Linked Comment: Taylor. Br J Dermatol 2020; 183 :413–414 . Abstract : What's already known about this topic? To date, few epidemiological studies have investigated mercury exposure in relation to skin cancer risk. What does this study add? We found that higher blood total and methylmercury levels are associated with a higher prevalence of nonmelanoma skin cancer. Linked Comment: Taylor. Br J Dermatol 2020; 183 :413–414 . Plain language summary available online